The Body and the Brain: Measuring Skin Conductance Responses to Understand the Emotional Experience - Christopoulos, Georgios I. (2016)
In this article, we introduce the method of measuring skin conductance responses (SCR) reflecting peripheral (bodily) signals associated with emotions, decisions, and eventually behavior. While measuring SCR is a well-established, robust, widely used, and relatively inexpensive method, it has been rarely utilized in organizational research. We introduce the basic aspects of SCR methodology and explain the behavioral significance of the signal, especially in connection with the emotional experience. Importantly, we describe in detail a specific research protocol (fear conditioning) that serves as an illustrative example to support the initial steps for organizational scholars who are new to the method. We also provide the related scripts for stimulus presentation and basic data analysis, as well as an instructional video, with the aim to facilitate the dissemination of SCR methodology to organizational research. We conclude by suggesting potential future research questions that can be addressed using SCR measurements.